Interface influence on structural properties of InAs/GaSb type-II superlattices - Kubacka-Traczyk, Justyna; Sankowska, Iwona; Kaniewski, Janusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Theoretical studies of interface impact on structural properties of InAs/GaSb type-II superlattices were carried out. Multilayer structures used for mid-infrared detection were considered. The superlattices examined consisted of 190 pairs of 9 monolayers (MLs) of InAs and 10 MLs of GaSb. Both types of interfaces, i.e., “GaAs-like” as well as “InSb-like”, were analyzed. The simulations were performed using dynamical theory of diffraction for different thicknesses of interface layers. The lattice mismatch was extracted from X-ray diffraction profiles. The analysis performed shows that the strain-balanced InAs/GaSb superlattice can be optimized by using thin InSb-like or GaAs-like interface layers simultaneously.
Optica Applicata, Vol. 39, 2009, nr 4, s. 875-879
Keywords: optyka; interface; II type superlattice; InAs/GaSb